The Trophic Status of the Lubuk Lampam Floodplain in South Sumatera, Indonesia - Jubaedah, Dade; Kamal, Mohammad Mukhlis; Muchsin, Ismudi; Hariyadi, Sigid (UI Scholars Hub, 2016)
The Lubuk Lampam floodplain’s ecosystem is naturally affected by the fluctuation of the water surface. This ecosystem also receives anthropogenic substances such as nutrients and other chemicals, especially from the oil palm plantation and its industrial processing activities. The main objective of this research was to determine the trophic status of the floodplain using the trophic level index (TLI) and Carlson’s trophic state index (TSI). The water quality and the fish samples were collected and analyzed from 7 stations representing various types of floodplain habitat. The results showed that the trophic status of Lubuk Lampam was hypereutrophic (very nutrient-rich). This was also supported by the high increase of the body weight (“b” value more than 3) and the high gonadosomatic index (GSI) of the studied fishes, i.e. Osteochilus vittatus 2.53-6.81% (male) and 3.00-15.86% (female); Helostoma temminckii 0.28-3.33% (male) and 1.30-10.43% (female); and Channa striata 0.33-0.59% (male) and 0.21-2.73% (female).